National health accounts: structure, trends and sustainability of health expenditure in Nigeria (2007)
This paper explored the structure of the contribution of different stakeholders to the financing of health care in Nigeria. The analysis was based on the National Health Accounts (NHA) 1998 to 2002 estimates for Nigeria. The main objective was to assess the viability of each stakeholder as a sustainable means of financing health provision in Nigeria. About two-thirds of health expenditure in Nigeria was directly financed by households, while public sector funding was less than half the amount committed by households. Third-party payment through health insurance represented a minuscule portion. A comparative analysis of the trend in the sources of income of households and revenue of government, revealed a wide disparity that suggested possible non-sustainability of their respective roles in health financing in Nigeria. Apart from the fact that the contributions of NGOs’ were very small, they were dependent on donor funds whose vagaries can significantly affect sustainability. Though, health insurance contributed minimally to health financing in Nigeria, its prospect in assuming a significant role appeared to be very bright. The progressive growth of health insurance contributions was an indication of the prospect of the recently introduced National Health Insurance Scheme (NHIS) in Nigeria. The NHIS represents a viable means of pooling resources in such a way that the burden of both the government and the households can be greatly relieved. Thus, the sustainability of financing health care in Nigeria may strongly depend on the extent to which the populace was covered by the health insurance plan.